PENERAPAN MODEL PEMBELAJARAN SQ3R UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS DAN MOTIVASI BELAJAR PESERTA DIDIK KELAS VII - ade tito; sidiq aulia rahman (Universitas Islam Nusantara, 2018)
The learning process that is still dominated by the teacher by applying the procedural learning process and the assumption of some students that mathematics is a difficult and tedious lesson leads to low mathematical creative thinking ability and learning motivation for students. SQ3R learning model is an alternative learning model that can improve mathematical creative thinking ability and increase students' learning motivation to find meaning from what is learned in learning activities. The purpose of this study are (1) To find out the application of the SQ3R learning model can improve the mathematical creative thinking ability of grade VII students. (2) To find out the application of the SQ3R learning model can increase students' learning motivation. This research was conducted in SMP DUA MEI Banjaran in February - May 2018. This study used Classroom Action Research (CAR) method which lasted for two cycles. The research instruments used were observation sheets, learning motivation and test questionnaires. The results of this study indicate an increase in mathematical creative thinking ability and learning motivation of students. This can be seen from the average value of students' mathematics learning scores in the first cycle of 2.74 to 3.08 with the percentage of learning completeness of students in the first cycle of 48% to 91.67%, as well as the learning motivation of students feeling happy with mathematics is 66.44%, there is a willingness and awareness of mathematics learning at 64.53% and 69.40%, being independent by 52% and having a boost of 49%.